Scanning of Organic Agricultural Products From Production and Market Side - Zaini Amin; Andry Andry (Politeknik Negeri Lampung, 2021)
This research aims to: scan organic agricultural products from the production side, by comparing production and revenue through the application of two kinds organic fertilizers formulation; and scan from the market side, by observing marketing channels, and consumer responses to organic products produced. Both organic fertilizer formulations are obtained through the Linear Programming (LP) application that was conducted in May 2018-July 2018. Research conducted by the method of action research. For plants that need planting sweet corn, spinach, kale, and beans by applying both formulations in two experimental plots, with an area of respectively 40 m2, 14 m2, 14 m2, and 40 m2. Then, from the market side, crop yields are distributed through institutions involved in the marketing of these commodities, and then market data is obtained. The results show that, in terms of farm production and analysis, the provision of production can be done at a more competitive price, as indicated by high crop productivity, and minimal fertilizer costs; and from the market side, shows that 80% of distribution takes place through channels that require the services of intermediary traders, and consumer responses show that organic farming products are better than conventional agricultural products that they consumed previously.Introduction